Ferroptosis as a New Mechanism in Parkinson’s Disease Therapy Using Traditional Chinese Medicine - Wu, Lijuan; Liu, Meijun; Liang, Jingtao; Li, Nannan; Yang, Dongdong; Cai, Junjie; Zhang, Yong; He, Yuan; Chen, Zhigang; Ma, Tao (Frontiers in Pharmacology, 2021)
Parkinson’s disease (PD) is one of the most common neurodegenerative diseases. To date, among medications used to treat PD, only levodopa exhibits a limited disease-modifying effect on early-onset PD, but it cannot delay the progression of the disease. In 2018, for the first time, the World Health Organization included traditional Chinese medicine (TCM) in its influential global medical compendium. The use of TCM in the treatment of PD has a long history. At present, TCM can help treat and prevent PD. Iron metabolism is closely associated with PD. Ferroptosis, which is characterized by the accumulation of lipid peroxides, is a recently discovered form of iron-dependent cell death. The research literature indicates that ferroptosis in dopaminergic neurons is an important pathogenetic mechanism of PD. TCM may thus play unique roles in the treatment of PD and provide new ideas for the treatment of PD by regulating pathways associated with ferroptosis.